2014
DOI: 10.3390/ijms150813135
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Shox2 Leads to Congenital Dysplasia of the Temporomandibular Joint in Mice

Abstract: Our previous study reported that inactivation of Shox2 led to dysplasia and ankylosis of the temporomandibular joint (TMJ), and that replacing Shox2 with human Shox partially rescued the phenotype with a prematurely worn out articular disc. However, the mechanisms of Shox2 activity in TMJ development remain to be elucidated. In this study, we investigated the molecular and cellular basis for the congenital dysplasia of TMJ in Wnt1-Cre; pMes-stop Shox2 mice. We found that condyle and glenoid fossa dysplasia occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 28 publications
2
17
1
Order By: Relevance
“…The animal procedure used in the present study was approved by the Institutional Animal Care and Use Committee (IACUC) of Fujian University of Traditional Chinese Medicine (Fuzhou, China). A total of 72 Wnt1-Cre ; pMes-stop shox2 ; pMes-stop Ihh mice, generated by crossing Wnt1-Cre ; pMes-stop shox2 mice ( 14 ) with pMes-stop Ihh mice, and a total of 72 wild-type mice were provided by the laboratory of Dr Yiping Chen (Department of Cell and Molecular Biology, Tulane University, New Orleans, LA, USA). The mice were exposed to a 12 h light/dark cycle in a temperature (22±1°C) and humidity (56±1%) controlled environment.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The animal procedure used in the present study was approved by the Institutional Animal Care and Use Committee (IACUC) of Fujian University of Traditional Chinese Medicine (Fuzhou, China). A total of 72 Wnt1-Cre ; pMes-stop shox2 ; pMes-stop Ihh mice, generated by crossing Wnt1-Cre ; pMes-stop shox2 mice ( 14 ) with pMes-stop Ihh mice, and a total of 72 wild-type mice were provided by the laboratory of Dr Yiping Chen (Department of Cell and Molecular Biology, Tulane University, New Orleans, LA, USA). The mice were exposed to a 12 h light/dark cycle in a temperature (22±1°C) and humidity (56±1%) controlled environment.…”
Section: Methodsmentioning
confidence: 99%
“…A previous study by our group showed that downregulation of the Ihh signaling pathway is one of the causes of congenital dysplasia of the TMJ in mice with short stature homeobox 2 (shox2) overexpression ( 14 ). Shox2, a member of shox gene family, is found only in vertebrates, suggesting its role in the development of the internal skeleton and its associated structures ( 4 , 13 , 14 ). The present study was conducted to determine whether overexpression of Ihh may rescue the shox2 overexpression-associated effects on the TMJ phenotype using a mouse model of Ihh and shox2 overexpression ( Wnt1-Cre ; pMes-stop shox2 ; pMes-stop Ihh mice).…”
Section: Introductionmentioning
confidence: 99%
“…Shox2 ‐deficient ( Shox2 −/− ) mice exhibit severe defects in a number of developing organs, as well as the TMJ dysplasia and ankylosis (Gu et al , ). Mice with overexpression of Shox2 in CNC cells ( Wnt1‐Cre ; pMes‐stopShox2 mice) show the dysplasia in the condyle and glenoid fossa after 2 weeks of age, following increased apoptosis and the upregulated expression of MMPs and downregulated expression of IHH signaling molecules, COLIA1 and COLIIA1 (Li et al , ). Mice with the replacement of the mouse Shox2 gene with the human SHOX gene ( Shox2 SHOX‐KI/KI mice) show increased apoptosis in the articular disk, following the decreased expression of COLIA1 and aggrecan, accompanied by increased MMP activities (Li et al , ).…”
Section: Mouse Models For Temporomandibular Joint Disorders (Tmd)mentioning
confidence: 99%
“…It was well‐established that elevated MMPs and ADAMTS were responsible for the degradation of ECM during IVD degeneration, which was characterized by the loss of collagen II and aggrecan in ECM . It has been reported that pMes‐stop SHOX2 in TMJ resulted in reduction of Col I, Col II, AGG, and Gli2, along with increased cell apoptosis, as well as enhanced MMPs (MMP9 and MMP13) activity in the condyle . Li et al also reported that the expression of collagen I decreased in the SHOX2 SHOX‐KI/KI TMJ disc, aggrecan decreased in the disc and condoyle of SHOX2 SHOX‐KI/KI TMJ.…”
Section: Discussionmentioning
confidence: 98%
“…14 It has been reported that pMes-stop SHOX2 in TMJ resulted in reduction of Col I, Col II, AGG, and Gli2, along with increased cell apoptosis, as well as enhanced MMPs (MMP9 and MMP13) activity in the condyle. 34 Li et al 30 also reported that the expression of collagen I decreased in the SHOX2 SHOX-KI/KI TMJ disc, aggrecan decreased in the disc and condoyle of SHOX2 SHOX-KI/KI TMJ. Furthermore, they found that MMP9 and MMP13 expression was enhanced in the articular disc of SHOX2 SHOX-KI/KI TMJ.…”
Section: Role Of Shox2 In the Development Of Intervertebralmentioning
confidence: 95%